Behaviour of concrete specimens retrofitted with bio-based polyurethane coatings under dynamic loads - Somarathna, H.M.C.C.; Raman, S.N.; Mohotti, D.; Mutalib, A.A.; Badrie, K.H. (Elsevier, 2021)
Experimental investigationwasconductedusingconcretespecimenstoassesstheeffectivenessofbiobasedpolyurethane(PU)coatingsynthesizedfrompalmkerneloilinenhancingthedynamicmechanical responseofconcretespecimensunderquasi-staticanddynamicloads.Thedynamicloadingcondition wassimulatedbyconductingthree-pointbendingtestsatastrainrateof0.067s 1,andsimultaneously, under quasi-static loading(strainrateof0.00033s 1)conditions .The application of PU layer(s)(either on the impact face, reface ,or on both faces of the concrete specimens)increases the dynamic resistance of theconcreteelement,whichcanbeenhancedbyincreasingcoatingthicknessoneitherfaceoftheconcreteelement.Underdynamicconditions,with10%of total coating thickness compared to the beam depth, strainduringultimatefailure,andstrainenergydensitywereenhancedsignificantlywithmarginalenhancementintheultimateflexuralstrength.PUcoatingdoesnotdebondduringultimatefailure of the test specimens which implies good adhesion characteristics, and even with minimum coating thickness(2.5%),drasticfragmentationeffectscanbereduced.Bio-basedPUisagreenmaterialandapplicationof PU coating provides available and sustainable technique for protecting concrete structures against dynamic loads.
Keywords: Bio-based Polyurethane elastomer; Coating thickness :Concrete; Dynamic loading; Retrofitting